2022
DOI: 10.1093/humrep/deac177
|View full text |Cite
|
Sign up to set email alerts
|

Human 1PN and 3PN zygotes recapitulate all morphokinetic events of normal fertilization but reveal novel developmental errors

Abstract: STUDY QUESTION Does mono- (1PN) and tri-pronuclear (3PN) fertilization recapitulate the morphokinetic changes of normal bi-pronuclear (2PN) fertilization? SUMMARY ANSWER Abnormal fertilization retraces the overall choreography of normal fertilization but reveals novel morphokinetic phenomena and raises scientifically and clinically relevant questions. WHAT IS KNOWN ALREADY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 36 publications
2
20
1
Order By: Relevance
“…However, number of blastocyst per cycle was no signi cantly difference between two groups (3.92 ± 3.55 vs. Both maternal and paternal ages were higher in cases involving 3PN fertilization in ICSI [13]. However, in this study although female and male's ages were signi cantly older in PGT-A cycles than PGT-M/SR cycles.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…However, number of blastocyst per cycle was no signi cantly difference between two groups (3.92 ± 3.55 vs. Both maternal and paternal ages were higher in cases involving 3PN fertilization in ICSI [13]. However, in this study although female and male's ages were signi cantly older in PGT-A cycles than PGT-M/SR cycles.…”
Section: Discussioncontrasting
confidence: 65%
“…In the 3PN embryos after ICSI, equal ratios of XXX and XXY were observed and no XYY embryos were present [12]. However, Time-lapse technology (TLT) has revealed extrusion of the second polar body was observed in a vast majority of 3PN zygotes (92.1%) in ICSI cycles [13].…”
Section: Discussionmentioning
confidence: 99%
“…Human data are scarce, but several clues suggest an implication of mechanical properties of the cortex in normal and abnormal human development. A polarized actin distribution in metaphase II oocytes ( Coticchio et al , 2014 ) and occasional fusion of the second polar body with the zygote, leading to the delayed formation of one extra pronucleus, are consistent with this hypothesis ( Ezoe et al , 2022 ). In addition, mouse and human data suggest that measurement of the mechanical responses of the zygote cortex and/or zona pellucida to suction through a micropipette can predict embryo viability in terms of development to the blastocyst stage ( Yanez et al , 2016 ), This opens novel methodology opportunities for embryo selection in assisted reproduction.…”
Section: Preparation For the First Mitosissupporting
confidence: 61%
“…This frequency is much higher than that reported in previous studies. Actually, the frequency of nucleation errors in human cleavage-stage embryos was reported to be 25-62% 11,30,31 . However, in these studies, the embryos were observed using time-lapse monitoring.…”
Section: Discussionmentioning
confidence: 99%